VLSI implementation of a parser for MPEG-2 systems program stream - Ashwin Pai Ballambettu. (2008)
This report presents the VLSI design and implementation of a Parser for Program Stream of MPEG2 System Layer. The MPEG2 Program Stream Syntax, the Parser architecture, HDL implementation, simulation, synthesis and design timing analysis are discussed in detail.